Breastfeeding, mixed or formula feeding at 9 months and the prevalence of iron deficiency and iron deficiency anemia in two cohorts of infants in China - Clark, Katy M. (J Pediatr, 2016)
OBJECTIVE: To assess associations between breastfeeding and iron status at 9 months in two samples of Chinese infants. STUDY DESIGN: Associations between feeding at 9 months (breastfed [BF] as sole milk source, mixed-fed [MF], or formula-fed [FF]) and iron deficiency anemia (IDA), iron deficiency (ID), and iron sufficiency were determined in infants from Zhejiang and Hebei provinces (ns = 142 and 813). ID was defined as body iron < 0 mg/kg, IDA as ID + hemoglobin < 110 g/L. Multiple logistic regression assessed associations between feeding pattern and iron status. RESULTS: Breastfeeding was associated with iron status (P-values < .001). In Zhejiang, 27.5% of BF infants had IDA compared with 0% of FF infants. The odds of ID/IDA were increased in BF and MF infants compared with FF: BF vs. FF odds ratio (OR): 28.8, 95% CI: 3.7–226.4; MF vs. FF OR: 11.0, 95% CI: 1.2–103.2. In Hebei, 44.0% of BF infants had IDA compared with 2.8% of FF infants. With covariable adjustment, odds of IDA were increased in BF and MF groups: BF vs. FF OR: 78.8, 95% CI: 27.2–228.1; MF vs. FF OR: 21.0, 95% CI: 7.3–60.9. CONCLUSIONS: In both cohorts, the odds of ID/IDA at 9 months were increased in BF and MF infants, and ID/IDA was common. Although the benefits of breastfeeding are indisputable, these findings add to the evidence that breastfeeding in later infancy identifies infants at risk for ID/IDA in many settings. Protocols for detecting and preventing ID/IDA in BF infants are needed. TRIAL REGISTRATION: ClinicalTrials.gov: NCT00642863 and NCT00613717